A Comprehensive Review on Crustaceans’ Immune System With a Focus on Freshwater Crayfish in Relation to Crayfish Plague Disease - Bouallegui, Younes (Frontiers in Immunology, 2021)
Freshwater crayfish immunity has received great attention due to the need for urgent conservation. This concern has increased the understanding of the cellular and humoral defense systems, although the regulatory mechanisms involved in these processes need updating. There are, however, aspects of the immune response that require clarification and integration. The particular issues addressed in this review include an overall description of the oomycete Aphanomyces astaci, the causative agent of the pandemic plague disease which affects freshwater crayfish, and an overview of crustaceans’ immunity with a focus on freshwater crayfish. It includes a classification system of hemocyte sub-types, the molecular factors involved in hematopoiesis and the differential role of the hemocyte subpopulations in cell-mediated responses, including hemocyte infiltration, inflammation, encapsulation and the link with the extracellular trap cell death pathway (ETosis). In addition, other topics discussed include the identity and functions of hyaline cells, the generation of neoplasia, and the emerging topic of the role of sessile hemocytes in peripheral immunity. Finally, attention is paid to the molecular execution of the immune response, from recognition by the pattern recognition receptors (PRRs), the role of the signaling network in propagating and maintaining the immune signals, to the effector elements such as the putative function of the Down syndrome adhesion molecules (Dscam) in innate immune memory.